Outcomes-Based Career Preparation Programs for Contemporary Student-Athletes - Kristina Navarro; Heather McCormick (Journal of Applied Sports Management, 2017)
Framed from a constructivist approach, this manuscript draws from Savickas’ (2005) Theory of Career Construction to assess programmatic development and mastery of learning outcomes in preparation for life after higher education. Utilizing a mixed-method approach, findings outline recommendations for campusbased practitioner programming informed from the voices of NCAA Division I football student-athletes.
Keywords: Career development; student-athletes; higher education; best practices